PENGARUH FINANCIAL DISTRESS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN KONSERVATISME AKUNTANSI SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2020-2022 - Rahmania, Wasilatul; Wahyuni, Ika; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2023)
The purpose of this study is to determine the effect of Financial Distress and Leverage on company Value with Accounting Conservatism as an intervening variable in Food and Beverage Companies listed on the Indonesia Stock Exchange 2020-2022. The population in this study is all Food and Beverage Companies listed on the Indonesia Stock Exchange in 2020-2022, a total of 30 companies. The sampling technique for this study used purposive sampling so that 10 samples were used as data analysis. The Data analysis and hypothesis testing used the Smart PLS 3.0 application. The results of this study indicate that Financial Distress has a positive but not significant effect on Accounting Conservatism, Leverage has a positive but not significant effect on Accounting Conservatism, Financial Distress has a negative but significant effect on company Value, Leverage has a negative but significant effect on company Value, Accounting Conservatism has a positive but not significant effect significant to company Value, Financial Distress has a positive but not significant effect on company Value through Accounting Conservatism, Leverage has a negative but not significant effect on company Value through Accounting Conservatism.